1 Chronicles: A commentary - Klein, Ralph W.; (1936-2021) (U.S.A, 2006)
This commentary takes full advantage of recent advances in the textual history of Samuel and Kings, demonstrating in many cases that the differences often ascribed to the Chronicler came in fact from the divergent copy of the canonical books he was rewriting. Klein brings to lively expression the unique theological voice of the Chronicler and demonstrates there have been far fewer secondary additions to the text than is normally assumed.
Keywords: Bible -- ST -- Book of Chronicles, 1 -- comments